CD(II) ION IMPRINTED POLYMER: SYNTHESIS, CHARACTERIZATION, AND ITS APPLICATION - Annisa Rahmah, Vindi
River water is an essential natural resource whose existence is often close to settlements and industrial factories. This increases the risk of river water contamination. One of the possible contaminants is cadmium heavy metal. The adsorption method is an effective, easy, and simple method to reduce contamination of toxic heavy metals such as cadmium in aquatic environments. The aim of this study is to synthesize and characterize Cd(II) ion-imprinted polymer. The adsorption process is carried out by utilizing the specificity of the introduction sites of the Cd(II) ion-imprinted polymer. Cadmium ion as a template reacts first to form a complex with ligand. A specific recognition site is formed by copolymerization between the monomer and the crosslinker in the presence of a template ion which is then released from the polymer to form a characteristic cavity that resembles the template ion in the imprinted polymer. The imprinted polymer was synthesized using several constituent components such as Cd(II) ions obtained from Cd(NO3)2.4H2O as a the template ion, 8-hydroxyquinoline as ligand, methyl methacrylate as monomer, ethylene glycol dimethacrylate as crosslinker, benzoyl peroxide as initiator, and ethanol : acetonitrile (2:1) as porogen. Synthesis of Cd(II) ion-imprinted polymer was carried out to obtain Cd-IIP, NIP, and NIP-Ligand as control polymer. Synthesis utilized microwave heating process. The polymer formed were characterized using several instruments, such as Fourier Transform Infra - Red (FTIR) and Scanning Electron Microscope - Energy Dispersive X-Ray (SEM-EDX). The results of FTIR showed typical absorption bands of a number of functional groups found in 8-hydroxyquinoline ligand at wave number 1453 cm-1 and 1359 cm-1, the functional group of aliphatic =C-H at wave number 1006 cm-1 and 937 cm-1 as well as functional group of C-O and carbonyl at wave number 1159 cm-1 and 1724 cm-1 to indicate the presence of methyl methacrylate monomer and ethylene glycol dimethacrylate crosslinker. The SEM image shows the polymer surface which is spherical, porous, and hollow in shape. The EDX spectrum shows the presence of cadmium in the synthesized polymer composition of 0,19% which was completely released after the 10 times leaching process with HNO3 4M. Cadmium adsorption using the synthesized Cd-IIP polymer reached optimum conditions at pH 6, contact time of 90 minutes, concentration of Cd(II) solution 20 mg/L, with adsorbent dose at 10 mg. The adsorption process followed the pseudo-second-order reaction kinetic model with constants rate at 0,097 mg/L.min. The adsorption process also followed the Langmuir adsorption isotherm model with Langmuir constant of 1,49 L/mg and the experimental adsorption capacity was 7,61 mg/g while the maximum Langmuir adsorption capacity was 7,78 mg/g. The synthesized Cd (II) ion imprinted polymer has three cycles of repeated use with %Recovery value of 88,42%; 87,49%; and 77,46%. The selectivity of the Cd-IIP polymer was tested against Cu(II) and Zn(II) in their binary solutions, showed that the distribution and selectivity coefficient of Cd were greater than its competitor. The application of synthesized Cd(II) ion imprinted polymer to river water samples was able to adsorb cadmium metal at three water sample points with adsorption percentage of 56,49%; 50,18%; and 49,94%. The amount of adsorbed Cd(II) metal content was measured using an Atomic Absorption Spectrophotometry (AAS) instrument expressed in absorbance and the Cd(II) concentration was determined using the standard calibration curve method expressed in mg/L.